KEDUDUKAN JAMINAN FIDUSIA SETELAH ADANYA PUTUSAN PAILIT DITINJAU DARI UNDANG-UNDANG NO. 37 TAHUN 2004 TENTANG KEPAILITAN DAN PKPU - tommy leonard (Ilmu Hukum Prima (IHP), 2019)
Increased economic development activities lead to the increases need for funding. Some business activities can finance its business activities through its own budget, and some do not have enough funds to finance it that they require funding from other parties. To maintain the smooth return of these funds, there must be a guarantee if in the future the debtor experiences bankrupt and break promises then the lender can hold and sell the collateral. In Article 1 Paragraph 1, UUJF is security rights over objects moving either tangible or intangible and immovable particular building can not be encumbered encumbrance. UUK-PKPU Article 1 (1) which states that: "bankruptcy is common to all the wealth confiscated the bankruptcy debtor and pemberesannya maintenance performed by curators under the supervision of the Supervisory Judge as set out in the legislation. In general, bankruptcy is the conditions faced by the debtor, in the form of a general confiscation of all his assets as a result of inability to pay off its debt payment obligations, to be distributed in proportion to its creditors. UUK-PKPU newly formed has a wider coverage in terms of norms, the scope of the material, and the process of settlement of debts. The purpose of this study was to determine how the provisions of fiduciary law in Indonesia, to find out how the provisions of the bankruptcy law in Indonesia and to know how to position fiduciary-PKPU after the birth of the Labor Law. The research approached the problem through legislation and regulations, and use supporting theory to complete this study and attempt to explain how the nature of normative legal fiduciary position after the bankruptcy decision-PKPU terms of the Labor Law.